Non-oriented electrical steel sheet and its manufacturing method

By increasing the number of grains in the {411} direction and using the grain growth technology caused by strain, the problem that existing non-directional electromagnetic steel sheets are difficult to obtain excellent magnetic properties on the full circumference average is solved, and low iron loss and high magnetic flux density are achieved on the full circumference average.

JP7667490B2Active Publication Date: 2025-04-23NIPPON STEEL CORPORATION
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2023507203
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-19
Filing Date
2022-03-18
Publication Date
2025-04-23
Estimated Expiration
2042-03-18

AI Technical Summary

Technical Problem

It is difficult to obtain excellent magnetic properties on the full circumference average of existing non-directional electromagnetic steel sheets.

Method used

By using the grain growth technique caused by strain, the number of grains in the {411} direction is increased to become the dominant direction, so that the grain growth consumes grains in the {111} direction by strain-induced grain growth, and a non-directional electromagnetic steel sheet with excellent full-circumferential average magnetic properties are prepared.

Benefits of technology

Excellent magnetic properties are achieved on the full circumference average, including low iron loss and high magnetic flux density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667490000001
    Figure 0007667490000001
  • Figure 0007667490000002
    Figure 0007667490000002
  • Figure 0007667490000003
    Figure 0007667490000003
Patent Text Reader

Abstract

This non-directional electromagnetic steel sheet has a prescribed chemical composition, and when, upon observing by EBSD in a plane parallel to the steel sheet surface, the total area is represented by Stot, the area of grains in the (411) orientation is represented by S411, the area of grains in the orientation in which the Taylor factor M is over 2.8 is represented by Styl, the total area of grains in the orientation in which the Taylor factor M is 2.8 or below is represented by Stra, the average KAM value of grains in the (411) orientation is represented by K411, and the average KAM value of grains in the orientation in which the Taylor factor M is over 2.8 is represented by Ktyl, satisfies the relationships 0.20 ≤ Styl / Stot ≤ 0.85, 0.05 ≤ S411 / Stot ≤ 0.80, S411 / Stra ≥ 0.50, and K411 / Ktyl ≤ 0.990.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-oriented electrical steel sheet and a manufacturing method thereof. This application claims priority based on Japanese Patent Application No. 2021-046056, filed on March 19, 2021, the contents of which are incorporated herein by reference. [Background technology]

[0002] Non-oriented electrical steel sheets are used, for example, in the iron cores of motors, and are required to have excellent magnetic properties, such as low core loss and high magnetic flux density, in a direction parallel to the sheet surface.

[0003] For this purpose, the easy axis of magnetization of the crystal ( <100> It is advantageous to control the texture of the steel sheet so that the {100} orientation, {110} orientation, {111} orientation, etc., coincide with the in-plane direction of the sheet. Regarding such texture control, many techniques have been disclosed for controlling the {100} orientation, {110} orientation, {111} orientation, etc., such as those described in Patent Documents 1 to 5.

[0004] Various methods have been devised for controlling the texture, including a technology that utilizes "strain-induced grain growth." Under specific conditions, strain-induced grain growth can suppress the accumulation of the {111} orientation, which does not have an easy axis of magnetization in the in-plane direction of the sheet, and is therefore effectively used in non-oriented electrical steel sheets. These technologies are disclosed in Patent Documents 6 to 10, etc.

[0005] However, while the conventional method can suppress the accumulation of the {111} orientation, the accumulation of the {110} <001> The Goss orientation (hereafter, Goss orientation) grows. The Goss orientation has better magnetic properties in one direction than the {111} orientation, but the magnetic properties are hardly improved on the average all around. Therefore, the conventional method has the problem that it is not possible to obtain excellent magnetic properties on the average all around. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 2017-193754 [Patent Document 2] Japanese Patent Application Publication No. 2011-111658 [Patent Document 3] International Publication No. 2016 / 148010 [Patent Document 4] Japanese Patent Application Publication No. 2018-3049 [Patent Document 5] International Publication No. 2015 / 199211 [Patent Document 6] Japanese Patent Publication No. 8-143960 [Patent Document 7] Japanese Patent Application Publication No. 2002-363713 [Patent Document 8] Japanese Patent Publication No. 2011-162821 [Patent Document 9] Japanese Patent Publication No. 2013-112853 [Patent Document 10] Japanese Patent No. 4029430 Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above-mentioned problems, an object of the present invention is to provide a non-oriented electrical steel sheet capable of obtaining excellent magnetic properties on average all around, and a method for manufacturing the same. [Means for solving the problem]

[0008] The present inventors have investigated a technique for forming a favorable texture for non-oriented electrical steel sheets by utilizing strain-induced grain growth. <uvw>We focused on the fact that crystal grains with the {411} orientation (hereafter referred to as the {411} orientation) are as resistant to distortion as crystal grains with the Goss orientation. In other words, by increasing the number of crystal grains with the {411} orientation compared to the Goss orientation at the stage before strain-induced grain growth occurs, the {411} orientation grains mainly encroach on the {111} orientation grains through strain-induced grain growth, and a non-oriented electrical steel sheet with the {411} orientation as the primary orientation is produced. In this way, it was found that the magnetic properties of the entire circumference average (average of the rolling direction, width direction, direction at 45 degrees to the rolling direction, and direction at 135 degrees to the rolling direction) are improved by making the {411} orientation the primary orientation.

[0009] The inventors also investigated a method for increasing the number of crystal grains with {411} orientation compared to crystal grains with Goss orientation at a stage before strain-induced grain growth occurs, and discovered a method in which grain-oriented electrical steel sheet is used, and the grain-oriented electrical steel sheet is cold-rolled in the width direction at a prescribed reduction rate, and then intermediate annealed and skin-pass rolled.

[0010] Based on these findings, the present inventors have conducted further intensive research and have arrived at the following aspects of the invention.

[0011] [1] According to one aspect of the present invention Non-oriented electrical steel base sheet is mass%. C: 0.0100% or less, Si: 1.50%~4.00%, One or more selected from the group consisting of Mn, Ni, Co, Pt, Pb, Cu, and Au: less than 2.50% in total; Sol.Al: 4.000% or less, S: 0.0400% or less, N: 0.0100% or less, Sn: 0.00%~0.40%, Sb: 0.00%~0.40%, P: 0.00%~0.40%, Cr: 0.000%~0.100%, B: 0.0000%~0.0050%, O: 0.0000% to 0.0200%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; When the Mn content (mass%) is [Mn], the Ni content (mass%) is [Ni], the Co content (mass%) is [Co], the Pt content (mass%) is [Pt], the Pb content (mass%) is [Pb], the Cu content (mass%) is [Cu], the Au content (mass%) is [Au], the Si content (mass%) is [Si], and the sol.Al content (mass%) is [sol.Al], the following formula (1) is satisfied, The balance has a chemical composition consisting of Fe and impurities, Furthermore, when observing the surface of the steel sheet by EBSD, the total area was S tot , the area of ​​the {411} oriented grains is S 411 The area of ​​oriented grains with a Taylor factor M of more than 2.8 according to the following formula (2) is defined as S tyl The total area of ​​oriented grains with the Taylor factor M of 2.8 or less is defined as S tra , the average KAM value of the {411} oriented grains is K 411 The average KAM value of the oriented grains having the Taylor factor M of more than 2.8 is K tyl Then, the following equations (3) to (6) are satisfied. Non-oriented electrical steel base sheet . ([Mn]+[Ni]+[Co]+[Pt]+[Pb]+[Cu]+[Au])-([Si]+[sol.Al])≦0.00% ···(1) M = (cosφ × cosλ) -1 (2) 0.20≦S tyl / S tot ≦0.85 (3) 0.05≦S 411 / S tot ≦0.80 (4) S 411 / S tra ≧0.50 (5) K 411 / K tyl ≦0.990 (6) Here, φ in equation (2) represents the angle between the stress vector and the crystal slip direction vector, and λ represents the angle between the stress vector and the normal vector of the crystal slip plane. [2] As described in [1] above Non-oriented electrical steel base sheet Further, the average KAM value of the oriented grains having the Taylor factor M of 2.8 or less is K tra In this case, the following formula (7) may be satisfied. K 411 / K tra <1.010 ···(7) [3] The above [1] or [2] Non-oriented electrical steel base sheet Furthermore, the area of ​​the {110} oriented grains is S 110 In this case, the following formula (8) may be satisfied. S 411 / S 110 ≧1.00 (8) Here, equation (8) is the area ratio S 411 / S 110 It is assumed that this holds true even if diverges to infinity. [4] Any one of the above items [1] to [3] Non-oriented electrical steel base sheet furthermore, the average KAM value of the {110} oriented grains is 110 In this case, the following formula (9) may be satisfied. K 411 / K 110 <1.010 ···(9) [5] According to another aspect of the present invention Non-oriented electrical steel base sheet teeth, In mass%, C: 0.0100% or less, Si: 1.50%~4.00%, One or more selected from the group consisting of Mn, Ni, Co, Pt, Pb, Cu, and Au: less than 2.50% in total; Sol.Al: 4.000% or less, S: 0.0400% or less, N: 0.0100% or less, Sn: 0.00%~0.40%, Sb: 0.00%~0.40%, P: 0.00%~0.40%, Cr: 0.000%~0.100%, B: 0.0000%~0.0050%, O: 0.0000% to 0.0200%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; When the Mn content (mass%) is [Mn], the Ni content (mass%) is [Ni], the Co content (mass%) is [Co], the Pt content (mass%) is [Pt], the Pb content (mass%) is [Pb], the Cu content (mass%) is [Cu], the Au content (mass%) is [Au], the Si content (mass%) is [Si], and the sol.Al content (mass%) is [sol.Al], the following formula (1) is satisfied, The balance has a chemical composition consisting of Fe and impurities, Furthermore, when observing the surface of the steel sheet by EBSD, the total area was S tot , the area of ​​the {411} oriented grains is S 411 The area of ​​oriented grains with a Taylor factor M of more than 2.8 according to the following formula (2) is defined as S tyl The total area of ​​oriented grains with the Taylor factor M of 2.8 or less is defined as S tra , the average KAM value of the {411} oriented grains is K 411 The average KAM value of the oriented grains having the Taylor factor M of more than 2.8 is K tyl , the average grain size in the observation area is d ave The average grain size of the {411} oriented grains is d 411 The average grain size of the oriented grains having the Taylor factor M of more than 2.8 is d tyl In this case, the following expressions (10) to (15) are satisfied. ([Mn]+[Ni]+[Co]+[Pt]+[Pb]+[Cu]+[Au])-([Si]+[sol.Al])≦0.00% ···(1) M = (cosφ × cosλ) -1 (2) S tyl / S tot ≦0.70 (10) 0.20≦S 411 / S tot (11) S 411 / S tra ≧0.55 (12) K 411 / K tyl ≦1.010 (13) d 411 / d ave >1.00 (14) d 411 / d tyl >1.00 (15) Here, φ in equation (2) represents the angle between the stress vector and the crystal slip direction vector, and λ represents the angle between the stress vector and the normal vector of the crystal slip plane. [6] As described in [5] above Non-oriented electrical steel base sheet Further, the average KAM value of the oriented grains having the Taylor factor M of 2.8 or less is K tra In this case, the following formula (16) may be satisfied. K 411 / K tra <1.010 ···(16) [7] [5] or [6] above Non-oriented electrical steel base sheet Further, the average crystal grain size of the oriented grains having the Taylor factor M of 2.8 or less is defined as d tra In this case, the following formula (17) may be satisfied. d 411 / d tra >1.00 (17) [8] Any one of the above [5] to [7] Non-oriented electrical steel base sheet Furthermore, the area of ​​the {110} oriented grains is S 110 In this case, the following formula (18) may be satisfied. S 411 / S 110 ≧1.00 (18) Here, equation (18) is the area ratio S 411 / S 110 It is assumed that this holds true even if diverges to infinity. [9] Any one of the above [5] to [8] Non-oriented electrical steel base sheet furthermore, the average KAM value of the {110} oriented grains is 110 In this case, the following formula (19) may be satisfied. K 411 / K 110 <1.010 ···(19)

[10] Any one of the above [1] to [9] Non-oriented electrical steel base sheet teeth, The chemical composition is, in mass%, Sn: 0.02%~0.40%, Sb: 0.02% to 0.40%, and P: One or more types selected from the group consisting of 0.02% to 0.40% may be contained.

[11] Any one of the above [1] to

[10] Non-oriented electrical steel base sheet The chemical composition may contain, in mass %, one or more elements selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0005% to 0.0100% in total.

[12] According to one aspect of the present invention Non-oriented electrical steel base sheet The manufacturing method of Any one of the above [1] to [4] Non-oriented electrical steel base sheet A method for producing In mass%, C: 0.0100% or less, Si: 1.50%~4.00%, One or more selected from the group consisting of Mn, Ni, Co, Pt, Pb, Cu, and Au: less than 2.50% in total; Sol.Al: 4.000% or less, S: 0.0400% or less, N: 0.0100% or less, Sn: 0.00%~0.40%, Sb: 0.00%~0.40%, P: 0.00%~0.40%, Cr: 0.000%~0.100%, B: 0.0000%~0.0050%, O: 0.0000% to 0.0200%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; When the Mn content (mass%) is [Mn], the Ni content (mass%) is [Ni], the Co content (mass%) is [Co], the Pt content (mass%) is [Pt], the Pb content (mass%) is [Pb], the Cu content (mass%) is [Cu], the Au content (mass%) is [Au], the Si content (mass%) is [Si], and the sol.Al content (mass%) is [sol.Al], the following formula (1) is satisfied, A step of cold rolling a grain-oriented electrical steel sheet having a chemical composition with the balance being Fe and impurities at a rolling reduction of 20% to 50% in the width direction; A step of subjecting the cold-rolled steel sheet to intermediate annealing at a temperature of 650°C or higher; A step of subjecting the steel sheet that has been subjected to the intermediate annealing to skin pass rolling at a rolling reduction of 5% to 30% in the same direction as the rolling direction of the cold rolling; has. ([Mn]+[Ni]+[Co]+[Pt]+[Pb]+[Cu]+[Au])-([Si]+[sol.Al])≦0.00% ···(1)

[13] According to another aspect of the present invention Non-oriented electrical steel base sheet The manufacturing method of Any one of the above [5] to [9] Non-oriented electrical steel base sheet A method for producing Any one of the above [1] to [4] Non-oriented electrical steel base sheet The material is subjected to heat treatment at a temperature of 700°C to 950°C for 1 to 100 seconds.

[14] A non-oriented electrical steel sheet according to another embodiment of the present invention comprises, in mass%, C: 0.0100% or less, Si: 1.50%~4.00%, One or more selected from the group consisting of Mn, Ni, Co, Pt, Pb, Cu, and Au: less than 2.50% in total; Sol.Al: 4.000% or less, S: 0.0400% or less, N: 0.0100% or less, Sn: 0.00%~0.40%, Sb: 0.00%~0.40%, P: 0.00%~0.40%, Cr: 0.000%~0.100%, B: 0.0000%~0.0050%, O: 0.0000% to 0.0200%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; When the Mn content (mass%) is [Mn], the Ni content (mass%) is [Ni], the Co content (mass%) is [Co], the Pt content (mass%) is [Pt], the Pb content (mass%) is [Pb], the Cu content (mass%) is [Cu], the Au content (mass%) is [Au], the Si content (mass%) is [Si], and the sol.Al content (mass%) is [sol.Al], the following formula (1) is satisfied, The balance has a chemical composition consisting of Fe and impurities, Furthermore, when observing the surface of the steel sheet by EBSD, the total area was S tot , the area of ​​the {411} oriented grains is S 411 The area of ​​oriented grains with a Taylor factor M of more than 2.8 according to the following formula (2) is defined as S tyl The total area of ​​oriented grains with the Taylor factor M of 2.8 or less is defined as S tra , the average grain size in the observation area is d ave The average grain size of the {411} oriented grains is d 411 The average grain size of the oriented grains having the Taylor factor M of more than 2.8 is d tyl A non-oriented electrical steel sheet that satisfies the following formulas (20) to (24). ([Mn]+[Ni]+[Co]+[Pt]+[Pb]+[Cu]+[Au])-([Si]+[sol.Al])≦0.00% ···(1) M = (cosφ × cosλ) -1 (2) S tyl / S tot <0.55 ···(20) S 411 / S tot >0.30 (21) S 411 / S tra ≧0.60 (22) d 411 / d ave ≧0.95 (23) d 411 / d tyl ≧0.95 (24) Here, φ in equation (2) represents the angle between the stress vector and the crystal slip direction vector, and λ represents the angle between the stress vector and the normal vector of the crystal slip plane.

[15] The non-oriented electrical steel sheet according to the above

[14] further comprises: a) a mean crystal grain size of oriented grains having a Taylor factor M of 2.8 or less; tra In this case, the following formula (25) may be satisfied. d 411 / d tra ≧0.95 (25)

[16] A method for producing a non-oriented electrical steel sheet according to another embodiment of the present invention comprises the steps of: A method for producing a non-oriented electrical steel sheet according to the above

[14] , Any one of the above [1] to

[11] Non-oriented electrical steel base sheet The material is subjected to heat treatment at a temperature of 950°C to 1050°C for 1 to 100 seconds, or at a temperature of 700°C to 900°C for more than 1000 seconds. Effect of the Invention

[0012] According to the above-described aspects of the present invention, it is possible to provide a non-oriented electrical steel sheet capable of obtaining excellent magnetic properties on average all around, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described. A non-oriented electrical steel sheet according to an embodiment of the present invention is manufactured by using a grain-oriented electrical steel sheet having a chemical composition described later as a raw material, through a cold rolling process in which the grain-oriented electrical steel sheet is cold-rolled in the width direction, an intermediate annealing process, and a skin-pass rolling process. A non-oriented electrical steel sheet according to another embodiment of the present invention is manufactured by a cold rolling process in which the grain-oriented electrical steel sheet is cold-rolled in the width direction, an intermediate annealing process, a skin-pass rolling process, and a first heat treatment process. A non-oriented electrical steel sheet according to another embodiment of the present invention is manufactured by a cold rolling process in which the grain-oriented electrical steel sheet is cold-rolled in the width direction, an intermediate annealing process, a skin-pass rolling process, a first heat treatment process performed as necessary, and a second heat treatment process. The heat treatment (first heat treatment and / or second heat treatment) after skin-pass rolling causes the steel sheet to undergo strain-induced grain growth and then normal grain growth. The strain-induced grain growth and normal grain growth may occur in the first heat treatment step or in the second heat treatment step. The steel sheet after skin-pass rolling is in a relationship with the base sheet of the steel sheet after strain-induced grain growth and the base sheet of the steel sheet after normal grain growth. Moreover, the steel sheet after strain-induced grain growth is in a relationship with the base sheet of the steel sheet after normal grain growth. Hereinafter, the steel sheet after skin-pass rolling, the steel sheet after strain-induced grain growth, and the steel sheet after normal grain growth, regardless of whether they are before or after heat treatment, will all be described as non-oriented electrical steel sheets. In this embodiment, by increasing the number of crystal grains centered on the {411} orientation (hereinafter, {411} orientation grains) compared to crystal grains centered on the Goss orientation (hereinafter, {110} orientation grains) in the metal structure of the steel sheet before skin pass rolling, the number of {411} orientation grains is increased in the subsequent heat treatment process, thereby improving the magnetic properties all around. The number of {411} orientation grains may be increased before skin pass rolling in a process other than that described above.

[0014] First, the chemical composition of the non-oriented electrical steel sheet according to this embodiment and the grain-oriented electrical steel sheet that is the raw material used in the manufacturing method thereof will be described. Since the chemical composition does not change by rolling or heat treatment, the chemical composition of the grain-oriented electrical steel sheet that is the raw material is the same as the chemical composition of the non-oriented steel sheet obtained through each process. In the following description, the unit of content of each element contained in the non-oriented electrical steel sheet or steel material, "%", means "mass %" unless otherwise specified. The non-oriented electrical steel sheet according to this embodiment and the grain-oriented electrical steel sheet that is the raw material thereof, have the following composition: C: 0.0100% or less, Si: 1.50% to 4.00%, one or more selected from the group consisting of Mn, Ni, Co, Pt, Pb, Cu, and Au: less than 2.50% in total, sol.Al: 4.000% or less, S: 0.0400% or less, N: 0.0100% or less, Sn: 0.00% to 0.40%, Sb: 0.00 % to 0.40%, P: 0.00% to 0.40%, Cr: 0.000% to 0.100%, B: 0.0000% to 0.0050%, O: 0.0000% to 0.0200%, and one or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total, with the balance being Fe and impurities. In addition, when the Mn content (mass%) is [Mn], the Ni content (mass%) is [Ni], the Co content (mass%) is [Co], the Pt content (mass%) is [Pt], the Pb content (mass%) is [Pb], the Cu content (mass%) is [Cu], the Au content (mass%) is [Au], the Si content (mass%) is [Si], and the sol.Al content (mass%) is [sol.Al], the following is satisfied: ([Mn]+[Ni]+[Co]+[Pt]+[Pb]+[Cu]+[Au])-([Si]+[sol.Al])≦0.00%. Examples of impurities include those contained in raw materials such as ores and scraps, and those contained in the manufacturing process. Also, instead of using grain-oriented electrical steel sheets, single crystals may be formed in a steel sheet having the above-mentioned chemical composition, and grains having the Goss orientation may be cut out and used as the material.

[0015] (C:0.0100% or less) C increases iron loss and causes magnetic aging. Therefore, the lower the C content, the better. This phenomenon is significant when the C content exceeds 0.0100%. For this reason, the C content is set to 0.0100% or less. There is no particular lower limit for the C content, but in consideration of the cost of decarburization during refining, it is preferable to set the C content to 0.0005% or more.

[0016] (Si: 1.50% to 4.00%) Silicon increases electrical resistance, decreases eddy current loss, and reduces iron loss, and increases the yield ratio to improve punching workability into iron cores. If the Si content is less than 1.50%, these effects cannot be fully obtained. Therefore, the Si content is set to 1.50% or more. On the other hand, if the Si content exceeds 4.00%, the magnetic flux density decreases, punching workability decreases due to an excessive increase in hardness, and cold rolling becomes difficult. Therefore, the Si content is set to 4.00% or less.

[0017] (One or more selected from the group consisting of Mn, Ni, Co, Pt, Pb, Cu, and Au: less than 2.50% in total) These elements are austenite phase (γ phase) stabilizing elements, and when contained in large amounts, ferrite-austenite transformation (hereinafter, α-γ transformation) occurs during heat treatment of the steel sheet. The effect of the non-oriented electrical steel sheet according to the present embodiment is believed to be exerted by controlling the area and area ratio of a specific crystal orientation in a cross section parallel to the steel sheet surface. However, if α-γ transformation occurs during heat treatment, the above area and area ratio change significantly due to the transformation, making it difficult to obtain a predetermined area ratio. For this reason, the total content of one or more elements selected from the group consisting of Mn, Ni, Co, Pt, Pb, Cu, and Au is limited to less than 2.50%. The total content is preferably less than 2.00%, more preferably less than 1.50%. There is no particular lower limit for the total content of these elements, but from the viewpoint of cost, it is preferably 0.0001% or more.

[0018] Furthermore, the following condition is also satisfied as a condition for preventing the α-γ transformation: the Mn content (mass%) is [Mn], the Ni content (mass%) is [Ni], the Co content (mass%) is [Co], the Pt content (mass%) is [Pt], the Pb content (mass%) is [Pb], the Cu content (mass%) is [Cu], the Au content (mass%) is [Au], the Si content (mass%) is [Si], and the sol.Al content (mass%) is [sol.Al], and the following formula (1) is satisfied: ([Mn]+[Ni]+[Co]+[Pt]+[Pb]+[Cu]+[Au])-([Si]+[sol.Al])≦0.00% ···(1)

[0019] (sol.Al:4.000% or less) Sol.Al increases electrical resistance, reduces eddy current loss, and reduces iron loss. Sol.Al also contributes to improving the relative magnitude of magnetic flux density B50 with respect to saturation magnetic flux density. Here, magnetic flux density B50 is magnetic flux density in a magnetic field of 5000A / m. If the sol.Al content is less than 0.0001%, these effects cannot be fully obtained. Furthermore, Al also has the effect of promoting desulfurization in steelmaking. Therefore, the sol.Al content is preferably 0.0001% or more. More preferably, it is 0.001% or more, and even more preferably, it is 0.300% or more. On the other hand, if the sol.Al content exceeds 4.000%, the magnetic flux density decreases, the yield ratio decreases, and the punching workability decreases. For this reason, the sol.Al content is set to 4.000% or less. The sol.Al content is preferably 2.500% or less, and even more preferably, it is set to 1.500% or less.

[0020] (S:0.0400% or less) S is not an essential element, and is contained, for example, as an impurity in steel. S inhibits recrystallization and grain growth during annealing by precipitation of fine MnS. Therefore, the lower the S content, the better. Such an increase in iron loss and a decrease in magnetic flux density due to the inhibition of recrystallization and grain growth are significant when the S content exceeds 0.0400%. For this reason, the S content is set to 0.0400% or less. The S content is preferably set to 0.0200% or less, more preferably 0.0100% or less. There is no particular lower limit for the S content, but in consideration of the cost of desulfurization treatment during refining, the S content is preferably set to 0.0003% or more.

[0021] (N:0.0100% or less) Like C, N deteriorates magnetic properties, so the lower the N content, the better. Therefore, the N content is set to 0.0100% or less. There is no particular lower limit for the N content, but considering the cost of denitrification treatment during refining, the N content is preferably set to 0.0010% or more.

[0022] (Sn:0.00%~0.40%, Sb:0.00%~0.40%, P:0.00%~0.40%) Excessive content of Sn, Sb, and P embrittle steel. Therefore, the Sn and Sb contents are each set to 0.40% or less, and the P content is set to 0.40% or less. On the other hand, Sn and Sb improve the texture after cold rolling and recrystallization, and increase the magnetic flux density. P contributes to ensuring the hardness of the steel sheet after recrystallization. Therefore, these elements may be contained as necessary. In order to impart further effects such as magnetic properties, it is preferable to contain one or more elements selected from the group consisting of 0.02% to 0.40% Sn, 0.02% to 0.40% Sb, and 0.02% to 0.40% P.

[0023] (One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total) Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn and Cd react with S in the molten steel during casting of the molten steel to form precipitates of sulfides or oxysulfides, or both. Hereinafter, Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn and Cd may be collectively referred to as "coarse precipitate forming elements". The particle size of the precipitates of the coarse precipitate forming elements is about 1 μm to 2 μm, which is much larger than the particle size (about 100 nm) of fine precipitates such as MnS, TiN and AlN. Therefore, these fine precipitates adhere to the precipitates of the coarse precipitate forming elements and are less likely to inhibit the growth of crystal grains in strain-induced grain growth. Therefore, these elements may be contained. In order to fully obtain the above effects, it is preferable that the total content of these elements is 0.0005% or more. On the other hand, if the total content of these elements exceeds 0.0100%, the total amount of sulfides or oxysulfides or both will be excessive, inhibiting the growth of crystal grains in strain-induced grain growth. Therefore, the total content of the elements that form coarse precipitates is set to 0.0100% or less.

[0024] (Cr:0.000%~0.100%) Cr combines with oxygen in the steel to produce Cr2O3. This Cr2O3 contributes to improving the texture. Therefore, Cr may be contained. To obtain the above effect, the Cr content is preferably 0.001% or more. On the other hand, if the Cr content exceeds 0.100%, Cr2O3 inhibits grain growth during annealing, resulting in fine crystal grains and an increase in iron loss, so the Cr content is set to 0.100% or less.

[0025] (B: 0.0000%~0.0050%) A small amount of B contributes to improving the texture, so B may be contained. To obtain the above effects, the B content is preferably 0.0001% or more. On the other hand, if the B content exceeds 0.0050%, the B compounds inhibit grain growth during annealing, resulting in fine crystal grains and an increase in iron loss. Therefore, the B content is set to 0.0050% or less.

[0026] (O:0.0000%~0.0200%) O combines with Cr in the steel to produce Cr2O3. This Cr2O3 contributes to improving the texture. Therefore, O may be contained. To obtain the above effect, the O content is preferably 0.0010% or more. On the other hand, if the O content exceeds 0.0200%, Cr2O3 inhibits grain growth during annealing, resulting in fine crystal grains and an increase in iron loss. Therefore, the O content is set to 0.0200% or less.

[0027] Next, the sheet thickness of the non-oriented electrical steel sheet according to the present embodiment will be described. The thickness (sheet thickness) of the non-oriented electrical steel sheet according to the embodiment is preferably 0.10 mm to 0.28 mm. If the thickness exceeds 0.28 mm, excellent high-frequency iron loss may not be obtained. Therefore, the thickness is preferably 0.28 mm or less. If the thickness is less than 0.10 mm, the influence of magnetic flux leakage from the surface of the non-oriented electrical steel sheet may become large, and the magnetic properties may deteriorate. Furthermore, if the thickness is less than 0.10 mm, it may be difficult to pass the sheet through the annealing line, or the number of non-oriented electrical steel sheets required for a certain size of iron core may increase, which may cause a decrease in productivity and an increase in manufacturing costs due to an increase in the number of steps. Therefore, the thickness is preferably 0.10 mm or more. More preferably, the thickness is 0.20 mm to 0.25 mm.

[0028] Next, the metal structure of the non-oriented electrical steel sheet according to the present embodiment will be described. Hereinafter, the non-oriented electrical steel sheet according to each embodiment will be specified by the metal structure after skin pass rolling, the metal structure after the first heat treatment, and the metal structure after the second heat treatment.

[0029] First, the metal structure to be identified and the method for identifying it will be described. The metal structure to be identified in this embodiment is identified in a cross section parallel to the sheet surface of the steel sheet, and is identified by the following procedure.

[0030] First, the sheet was polished to expose the center of the sheet thickness, and the polished surface (parallel to the steel sheet surface) was analyzed by EBSD (Electron Back Scattering Diffraction) at 2500μm 2 Observation is performed on the above areas. The total area of ​​observation is 2500 μm 2 If it is more than this, it may be performed at several locations divided into several small sections. The step interval during measurement is preferably 50 to 100 nm. The following types of areas, KAM (Kernel Average Misorientation) values, and average crystal grain size are obtained from the EBSD observation data using general methods.

[0031] S tot : Total area (observation area) S tyl : The total area of ​​oriented grains with a Taylor factor M of more than 2.8 according to the following formula (2) S tra : The total area of ​​oriented grains with a Taylor factor M of 2.8 or less according to the following formula (2) S 411 : Total area of ​​{411} oriented grains S 110 : Total area of ​​{110} oriented grains K tyl : Average KAM value of oriented grains with Taylor factor M exceeding 2.8 according to the following formula (2) K tra : The average KAM value of oriented grains with a Taylor factor M of 2.8 or less according to the following formula (2) K 411 : Average KAM value of {411} oriented grains K 110 : Average KAM value of {110} oriented grains d ave : Average grain size in the observation area d 411 : Average grain size of {411} oriented grains d tyl Average grain size of grains with Taylor factor M exceeding 2.8 according to the following formula (2) d tra Average grain size of oriented grains for which the Taylor factor M according to the following formula (2) is 2.8 or less Here, the orientation tolerance of the crystal grains is set to 15°. In addition, when oriented grains are generated later, the orientation tolerance is also set to 15°.

[0032] Here, the Taylor factor M is assumed to comply with the following equation (2). M = (cosφ × cosλ) -1 (2) φ: Angle between the stress vector and the crystal slip vector λ: Angle between the stress vector and the normal vector of the crystal slip plane

[0033] The Taylor factor M is calculated based on the slip deformation of the crystal in the slip plane {110} and the slip direction <111> This is the Taylor factor when compressive deformation in the thickness direction occurs with in-plane strain in a plane parallel to the thickness direction and rolling direction. Hereinafter, unless otherwise specified, the average value of the Taylor factor according to formula (2) calculated for all crystallographically equivalent crystals will be simply referred to as the "Taylor factor".

[0034] Next, in the following embodiments 1 to 3, the features are defined by the above-mentioned area, KAM value, and average crystal grain size.

[0035] (Embodiment 1) First, the metal structure of the non-oriented electrical steel sheet after skin-pass rolling will be explained. This metal structure has accumulated strain sufficient to cause strain-induced grain growth, and can be considered as the initial stage before strain-induced grain growth occurs. The characteristics of the metal structure of the steel sheet after skin-pass rolling are roughly determined by the orientation for the development of crystal grains in the desired orientation and the conditions related to the strain sufficiently accumulated to cause strain-induced grain growth.

[0036] In the non-oriented electrical steel sheet according to this embodiment, the area of ​​each orientation grain satisfies the following formulas (3) to (5). 0.20≦S tyl / S tot ≦0.85 (3) 0.05≦S 411 / S tot ≦0.80 (4) S 411 / S tra ≧0.50 (5)

[0037] S tyl is the abundance of orientations with sufficiently large Taylor factors. In the strain-induced grain growth process, orientations with small Taylor factors and little accumulation of strain due to processing grow preferentially while eroding orientations with large Taylor factors and accumulated strain due to processing. For this reason, in order to develop special orientations by strain-induced grain growth, S tyl In this embodiment, the area ratio S tyl / S tot The area ratio S tyl / S tot The area ratio S is 0.20 or more. tyl / S tot If the area ratio S is less than 0.20, the desired crystal orientation will not be sufficiently developed due to strain-induced grain growth. tyl / S tot is 0.30 or more, more preferably 0.50 or more.

[0038] Area ratio S tyl / S tot The upper limit of is related to the amount of grains with the crystal orientation that should be developed in the strain-induced grain growth process described below, but the condition is not simply determined by the ratio of the orientations that grow preferentially and the orientations that are encroached upon. First, as described later, the area ratio S of {411}-oriented grains that should be developed in strain-induced grain growth is 411 / S tot Since is 0.05 or more, the area ratio S tyl / S tot However, the area ratio S tyl / S tot When the amount of is excessive, the preferential growth of the {411} oriented grains does not occur due to the relationship with the amount of strain described later. tyl / S tot is 0.85 or less. It is preferable that the area ratio S tyl / S tot is 0.75 or less, more preferably 0.70 or less.

[0039] In the subsequent strain-induced grain growth process, the {411} orientation grains are preferentially grown. The {411} orientation is one of the orientations in which the Taylor factor is sufficiently small and strain due to processing is unlikely to accumulate, and is an orientation that can grow preferentially in the strain-induced grain growth process. In this embodiment, the presence of {411} orientation grains is essential, and in this embodiment, the area ratio S of the {411} orientation grains is 411 / S tot The area ratio of {411} oriented grains S 411 / S tot If the area ratio S is less than 0.05, the {411} oriented grains will not develop sufficiently due to the subsequent strain-induced grain growth. 411 / S tot is 0.10 or more, more preferably 0.20 or more.

[0040] Area ratio S 411 / S tot The upper limit of is determined according to the amount of crystal orientation grains that should be eaten by strain-induced grain growth. In this embodiment, the area ratio S of the orientations that have a Taylor factor of more than 2.8 that should be eaten by strain-induced grain growth is tyl / S tot Since the area ratio S is 0.20 or more, 411 / S tot The area ratio S is preferably 0.80 or less. However, the effect is more pronounced if the amount of {411} oriented grains before strain-induced grain growth is low, and the {411} oriented grains can be developed more. Considering this, the area ratio S is preferably 0.80 or less. 411 / S tot is 0.60 or less, more preferably 0.50 or less, and further preferably 0.40 or less.

[0041] The explanation has focused on the {411} oriented grains as the grain orientation that should be preferentially grown, but there are many other grain orientations that, like the {411} oriented grains, have sufficiently small Taylor factors that make it difficult for strain due to processing to accumulate, and that can grow preferentially in strain-induced grain growth. Among these, the {110} orientation is one that is likely to exist in non-oriented electrical steel sheets. This orientation grain competes with the {411} oriented grains that should be preferentially grown. On the other hand, this orientation grain is oriented in the direction of the easy axis of magnetization ( <100> Since the number of grains with the {411} orientation is not as large as that of grains with the {411} orientation, if these orientations develop due to strain-induced grain growth, the magnetic properties will deteriorate, which is undesirable. For this reason, in this embodiment, the Taylor factor is specified to ensure the abundance ratio of grains with the {411} orientation among orientations with a sufficiently small Taylor factor that is unlikely to accumulate strain due to processing.

[0042] In the present invention, the area of ​​grains with a Taylor factor of 2.8 or less, including grains that are thought to compete with {411} grains in strain-induced grain growth, is defined as S tra Then, as shown in equation (5), the area ratio S 411 / S tra is set to 0.50 or more to ensure the dominance of the growth of {411} oriented grains. 411 / S tra If the area ratio S is less than 0.50, the {411} oriented grains do not develop sufficiently due to strain-induced grain growth. 411 / S tra is 0.80 or more, more preferably 0.90 or more. 411 / S tra There is no need to specify an upper limit for the Taylor factor of 2.8 or less. All grains with the orientation of {411} (S 411 / S tra =1.00).

[0043] Furthermore, in this embodiment, the relationship with the {110} orientation grains, which are known to be an orientation that is easy to grow by strain-induced grain growth, is specified. The {110} orientation is relatively easy to develop even in general methods such as increasing the crystal grain size in a hot-rolled steel sheet and then recrystallizing by cold rolling, or by cold rolling at a relatively low rolling reduction, and is an orientation that should be particularly considered in competition with the {411} orientation grains, which should be preferentially grown. If the {110} orientation grains develop by strain-induced grain growth, the in-plane anisotropy of the properties of the steel sheet will become very large, which is inconvenient. For this reason, in this embodiment, the area ratio S of the {411} orientation grains to the {110} orientation grains is set to 1 / 100, which is the ratio of the area of ​​the {411} orientation grains to the area of ​​the {110} orientation grains. 411 / S 110 It is preferable to ensure the dominance of the growth of the {411} oriented grains by satisfying equation (8). S 411 / S 110 ≧1.00 (8)

[0044] To more reliably prevent the inadvertent development of {110} oriented grains due to strain-induced grain growth, the area ratio S 411 / S 110 is preferably 1.00 or more. More preferably, the area ratio S 411 / S 110 is 2.00 or more, and more preferably 4.00 or more. 411 / S 110 There is no need to limit the upper limit of the area ratio S 411 / S 110 It is assumed that this holds true even if diverges to infinity.

[0045] In this embodiment, in addition to the above crystal orientation, the following distortion can be combined to obtain more excellent magnetic properties. In this embodiment, the following formula (6) must be satisfied as a rule regarding distortion. K 411 / K tyl ≦0.990 (6)

[0046] The requirement for strain is stipulated by equation (6), which is the ratio of the strain (average KAM value) accumulated in {411} oriented grains to the strain (average KAM value) accumulated in oriented grains with a Taylor factor of more than 2.8. Here, the KAM value is the orientation difference between adjacent measurement points within the same grain, and the KAM value is high at locations with a large amount of strain. From a crystallographic point of view, for example, when compressive deformation is performed in the thickness direction in a state of plane strain in a plane parallel to the thickness direction and rolling direction, that is, when a steel sheet is simply rolled, this K 411 and K. tyl Compared to K 411 / K tyl is smaller than 1. However, in reality, due to the influence of constraints from neighboring crystal grains, precipitates present within the crystal grains, and even macroscopic deformation fluctuations including contact with tools (rolling rolls, etc.) during deformation, the strain observed microscopically according to the crystal orientation takes on a variety of forms. For this reason, the purely geometrical orientation effect due to the Taylor factor is difficult to detect. Furthermore, even for grains with the same orientation, very large variations can occur depending on the grain size, grain shape, the orientation and grain size of neighboring grains, the state of precipitates, and the position in the plate thickness direction. Furthermore, even within a single crystal grain, the strain distribution can vary greatly due to the formation of deformation bands near and within the grains, etc.

[0047] In consideration of such fluctuations, in order to obtain excellent magnetic properties in this embodiment, K 411 / K tyl is 0.990 or less. 411 / K tyl If K exceeds 0.990, the specificity of the region to be encroached is lost, so that strain-induced grain growth is difficult to occur. 411 / K tyl is 0.970 or less, more preferably 0.950 or less.

[0048] In competition with the {411} oriented grains that should be preferentially grown, it is preferable that the relationship with the oriented grains having a Taylor factor of 2.8 or less satisfies formula (7). K 411 / K tra <1.010 ···(7)

[0049] For the preferential growth of {411} oriented grains, K 411 / K tra It is preferable to set K to less than 1.010. 411 / K tra is also an index of competition between orientations that are less likely to accumulate strain and have the potential for preferential growth, and K 411 / K tra If K is more than 1.010, the priority of the {411} orientation in strain-induced grain growth is not exhibited, and the desired crystal orientation does not develop. 411 / K tra is preferably 0.970 or less, and more preferably 0.950 or less.

[0050] In the competition with the {411} oriented grains, which should be preferentially grown, it is preferable to consider the relationship with the {110} oriented grains in terms of distortion as well as area. In this relationship, the ratio of the average KAM value of the {411} oriented grains to that of the {110} oriented grains, K 411 / K 110 It is preferable to ensure the dominance of the growth of the {411} oriented grains by satisfying equation (9). K 411 / K 110 <1.010 ···(9)

[0051] To more reliably prevent the inadvertent development of {110} oriented grains due to strain-induced grain growth, 411 / K 110 is preferably less than 1.010. More preferably, K 411 / K 110 is 0.970 or less, more preferably 0.950 or less.

[0052] In formula (9), if there are no crystal grains having an orientation corresponding to the denominator, the formula is not evaluated numerically and is considered to be satisfied.

[0053] In the metal structure of the non-oriented electrical steel sheet after skin pass rolling in this embodiment, the grain size is not particularly limited. This is because the relationship with the grain size is not so strong in the state where appropriate strain-induced grain growth occurs by the subsequent first heat treatment. In other words, whether the desired appropriate strain-induced grain growth occurs can be determined almost entirely by the relationship between the abundance (area) of each crystal orientation and the relationship between the amount of strain for each orientation, in addition to the chemical composition of the steel sheet.

[0054] However, if the crystal grain size becomes too coarse, sufficient grain growth is difficult to occur in a practical temperature range, even though it is induced by strain. In addition, if the crystal grain size becomes too coarse, it becomes difficult to avoid deterioration of magnetic properties. For this reason, it is preferable that the practical average crystal grain size is 300 μm or less. More preferably, it is 100 μm or less, even more preferably, it is 50 μm or less, and particularly preferably, it is 30 μm or less. The finer the crystal grain size, the easier it is to recognize the development of the desired crystal orientation due to strain-induced grain growth when the crystal orientation and strain distribution are appropriately controlled. However, if it becomes too fine, it becomes difficult to form a difference in the amount of strain for each crystal orientation due to the constraint with adjacent grains in the processing to impart strain as described above. From this viewpoint, the average crystal grain size is preferably 3 μm or more, more preferably, 8 μm or more, and even more preferably, 15 μm or more.

[0055] (Embodiment 2) Next, the metal structure of the non-oriented electrical steel sheet after strain-induced grain growth occurs (before strain-induced grain growth is completed) due to heat treatment (first heat treatment) will be described. In the non-oriented electrical steel sheet according to this embodiment, at least a portion of the strain is released by strain-induced grain growth, and the characteristics of the metal structure of the steel sheet after strain-induced grain growth are determined by the crystal orientation, strain, and grain size.

[0056] The crystal orientation in this embodiment satisfies the following formulas (10) to (12). These regulations have different numerical ranges compared to the formulas (3) to (5) related to the non-oriented electrical steel sheet after skin-pass rolling described above. This is because, with strain-induced grain growth, {411} orientation grains grow preferentially and their area increases, while orientation grains with a Taylor factor of more than 2.8 are mainly encroached upon by {411} orientation grains and their area decreases. S tyl / S tot ≦0.70 (10) 0.20≦S 411 / S tot (11) S 411 / S tra ≧0.55 (12)

[0057] Area ratio S tyl / S tot The upper limit of the area ratio S is determined as one of the parameters that indicates the degree of progress of strain-induced grain growth. tyl / S tot The fact that the area ratio S is greater than 0.70 indicates that the crystal grains of the orientation grains with a Taylor factor of greater than 2.8 are not sufficiently encroached, and strain-induced grain growth does not occur sufficiently. In other words, the {411} orientation grains that should be developed are not sufficiently developed, and therefore the magnetic properties are not sufficiently improved. Therefore, in this embodiment, the area ratio S tyl / S tot is set to 0.70 or less. It is preferable that the area ratio S tyl / S tot is 0.60 or less, more preferably 0.50 or less. tyl / S tot Since a smaller value is preferable, there is no need to specify a lower limit, and the lower limit may be 0.00.

[0058] In this embodiment, the area ratio S 411 / S tot The area ratio S is 0.20 or more. 411 / S tot The lower limit of the area ratio S is determined as one of the parameters that indicates the degree of progress of strain-induced grain growth. 411 / S tot If the area ratio S is less than 0.20, the development of the {411} oriented grains is insufficient, and the magnetic properties are not sufficiently improved. 411 / S tot is 0.40 or more, more preferably 0.60 or more. 411 / S tot Since a higher value is preferable, there is no need to specify an upper limit, and the upper limit may be 1.00.

[0059] As in the first embodiment, the relationship between the {411} oriented grains and the other grains that are thought to compete with the {411} oriented grains in strain-induced grain growth is also important. 411 / S tra When the area ratio S is large, the growth of the {411} oriented grains is favored, resulting in good magnetic properties. 411 / S tra The fact that the area ratio S is less than 0.55 indicates that the {411} oriented grains are not sufficiently developed due to strain-induced grain growth, and the grains with a Taylor factor exceeding 2.8 are encroached upon by grains with smaller Taylor factors other than the {411} oriented grains. In this case, the in-plane anisotropy of the magnetic properties also becomes large. Therefore, in this embodiment, the area ratio S 411 / S tra is 0.55 or more. It is preferable that the area ratio S 411 / S tra is 0.65 or more, more preferably 0.75 or more. 411 / S tra There is no need to particularly limit the upper limit, and all grains having a Taylor factor of 2.8 or less may be grains having the {411} orientation.

[0060] Furthermore, in this embodiment, the relationship with the {110} oriented grains is also specified as in the first embodiment. In this embodiment, the area ratio S of the {411} oriented grains to the {110} oriented grains is 411 / S 110 It is preferable that satisfies the following formula (18) so that the dominance of the growth of the {411} oriented grains is ensured. S 411 / S 110 ≧1.00 (18)

[0061] As shown in equation (18), in this embodiment, the area ratio S 411 / S 110 It is preferable that the area ratio S be 1.00 or more. The {110} oriented grains develop by strain-induced grain growth, and the area ratio S 411 / S 110 If the area ratio S is less than 1.00, the anisotropy in the steel sheet surface becomes very large, which tends to cause problems in terms of characteristics. 411 / S 110 is 2.00 or more, and more preferably 4.00 or more. 411 / S 110 There is no need to limit the upper limit of the area ratio of {110} grains, and the area ratio of {110} grains may be zero. 411 / S 110 It is assumed that this holds true even if diverges to infinity.

[0062] Next, the specifications regarding the strain that should be satisfied in this embodiment will be described. The amount of strain in the non-oriented electrical steel sheet according to this embodiment is significantly reduced compared to the amount of strain after skin-pass rolling described in embodiment 1, and the amount of strain for each crystal orientation is characteristic.

[0063] The definition of the strain in this embodiment has a different numerical range compared to the formula (6) related to the non-oriented electrical steel sheet after skin pass rolling described above, and satisfies the following formula (13). K 411 / K tyl ≦1.010 (13)

[0064] When strain-induced grain growth has progressed sufficiently, the large strain portions of the steel sheet are released, the strain for each crystal orientation is homogenized, the strain variation becomes sufficiently small, and the ratio shown in equation (13) becomes close to 1.

[0065] In consideration of such fluctuations, in order to obtain excellent magnetic properties in this embodiment, K 411 / K tyl is 1.010 or less. 411 / K tyl If K exceeds 1.010, the strain is not sufficiently released, and the reduction in iron loss in particular becomes insufficient. 411 / K tyl is 0.990 or less, more preferably 0.970 or less. Even if the non-oriented electrical steel sheet according to the present embodiment is obtained by performing the first heat treatment on a steel sheet satisfying the above-mentioned formula (6), the value of formula (13) may exceed 1.000 due to measurement errors, etc.

[0066] In competition with the {411} oriented grains that should be preferentially grown, it is preferable that the relationship with the oriented grains having a Taylor factor of 2.8 or less satisfies formula (16). K 411 / K tra <1.010 ···(16)

[0067] For the preferential growth of {411} oriented grains, K 411 / K tra It is preferable to set K to less than 1.010. 411 / K tra If the ratio is 1.010 or more, the release of strain is insufficient, and in particular the reduction in iron loss becomes insufficient. By subjecting the non-oriented electrical steel sheet satisfying the above-mentioned formula (7) to the first heat treatment, a non-oriented electrical steel sheet satisfying the formula (16) is obtained.

[0068] In the first embodiment, it was explained that it is preferable to consider the relationship with the strain of the {110} oriented grains. On the other hand, in the present embodiment, the strain-induced grain growth has progressed sufficiently and a large part of the strain in the steel sheet has been released. Therefore, the K 110 The value of K 411 It is preferable that the expression (19) is satisfied, similarly to the expression (9). K 411 / K 110 <1.010 ···(19)

[0069] In other words, similar to equation (9), K 411 / K 110 It is preferable that K is less than 1.010. 411 / K 110 If the ratio is 1.010 or more, the release of strain may be insufficient, and in particular the reduction in iron loss may be insufficient. Furthermore, by subjecting a non-oriented electrical steel sheet satisfying the above-mentioned formula (9) to the first heat treatment, a non-oriented electrical steel sheet satisfying the formula (19) is obtained.

[0070] In formulas (13) and (19), if there are no crystal grains having an orientation corresponding to the denominator, the formula is considered to be satisfied without being evaluated numerically.

[0071] Next, the regulations regarding the crystal grain size that must be satisfied in this embodiment will be explained. In a metal structure in which strain-induced grain growth has progressed sufficiently and large strain areas have been released, the crystal grain size for each crystal orientation has a significant effect on the magnetic properties. The crystal grains in the orientation that grows preferentially due to strain-induced grain growth become coarse, and the crystal grains in the orientation that are encroached upon by this become fine. In this embodiment, the relationship between the average crystal grain size must satisfy formulas (14) and (15). d 411 / d ave >1.00 (14) d 411 / d tyl >1.00 (15)

[0072] These formulas are the average grain size d of the grains with the {411} orientation, which is the preferred growth orientation. 411 is relatively large. These ratios in formulas (14) and (15) are preferably 1.30 or more, more preferably 1.50 or more, and even more preferably 2.00 or more. There are no particular limitations on the upper limits of these ratios, but because the crystal grains of the orientation to be eroded also grow during the first heat treatment, although their growth rate is slower than that of the {411} orientation grains, the above ratios are unlikely to become excessively large, and a practical upper limit is about 10.00.

[0073] In this embodiment, it is preferable to satisfy formula (17). d 411 / d tra >1.00 (17)

[0074] This formula is the average grain size d of the grains with the {411} orientation, which is the preferred growth orientation. 411 is relatively large. The ratio in formula (17) is more preferably 1.30 or more, even more preferably 1.50 or more, and particularly preferably 2.00 or more. There is no particular upper limit to this ratio, but since the crystal grains of the orientation to be eroded also grow during the first heat treatment, although their growth rate is slower than that of the {411} orientation grains, the above ratio is unlikely to become excessively large, and a practical upper limit is about 10.00.

[0075] Although the range of the average crystal grain size is not particularly limited, if the average crystal grain size becomes too coarse, it becomes difficult to avoid the deterioration of the magnetic properties. Therefore, in this embodiment, the practical average crystal grain size of the {411} orientation grains, which are relatively coarse grains, is preferably 500 μm or less. More preferably, the average crystal grain size of the {411} orientation grains is 400 μm or less, even more preferably 300 μm or less, and particularly preferably 200 μm or less. On the other hand, the lower limit of the average crystal grain size of the {411} orientation grains is preferably 40 μm or more, more preferably 60 μm or more, and even more preferably 80 μm or more, assuming that sufficient preferential growth of the {411} orientation is ensured.

[0076] In formula (15), if there are no crystal grains having an orientation corresponding to the denominator, the formula is not evaluated numerically and is considered to be satisfied.

[0077] (Embodiment 3) In the above-mentioned first and second embodiments, the characteristics of the steel sheet are specified by specifying the strain of the steel sheet by the KAM value. In contrast, in the present embodiment, the steel sheet described in the first or second embodiment is specified as a steel sheet obtained by annealing the steel sheet for a sufficiently long time and further growing the grains. In such a steel sheet, the strain-induced grain growth is almost completed, and as a result, the strain is almost completely released, so that the characteristics are very favorable. In other words, a steel sheet in which {411} orientation grains are grown by strain-induced grain growth, and normal grain growth is further performed by the second heat treatment until the strain is almost completely released becomes a steel sheet with stronger accumulation in the {411} orientation. In the present embodiment, the crystal orientation and crystal grain size of a steel sheet obtained by performing the second heat treatment using the steel sheet described in the first or second embodiment as a material (i.e., a non-oriented electrical steel sheet obtained by performing the first heat treatment and then the second heat treatment on a non-oriented electrical steel sheet after skin-pass rolling, or a non-oriented electrical steel sheet obtained by omitting the first heat treatment and performing the second heat treatment) will be described.

[0078] The crystal orientation of the steel sheet obtained by the second heat treatment satisfies the following formulas (20) to (22). These regulations have different numerical ranges compared to the formulas (3) to (5) for the non-oriented electrical steel sheet after skin-pass rolling and the formulas (10) to (12) for the non-oriented electrical steel sheet after strain-induced grain growth by the first heat treatment. This is because, with the strain-induced grain growth and the subsequent second heat treatment, the {411} orientation grains grow further and their area increases, while the orientation grains with a Taylor factor of more than 2.8 are mainly encroached upon by the {411} orientation grains and their area further decreases. S tyl / S tot <0.55 ···(20) S 411 / S tot >0.30 (21) S 411 / S tra ≧0.60 (22)

[0079] In this embodiment, the area ratio S tyl / S tot is less than 0.55. Total area S tyl may be zero. Area ratio S tyl / S tot The upper limit of the area ratio S is determined as one of the parameters that indicates the degree of growth of the {411} orientation grains. tyl / S tot When the area ratio S is 0.55 or more, it indicates that the oriented grains having a Taylor factor of more than 2.8, which should be increased at the stage of strain-induced grain growth, are not sufficiently increased. In this case, the magnetic properties are not sufficiently improved. tyl / S tot is 0.40 or less, more preferably 0.30 or less. tyl / S tot Since it is preferable that is small, the lower limit is not specified and may be 0.00.

[0080] In this embodiment, the area ratio S 411 / S tot is more than 0.30. Area ratio S 411 / S tot If the area ratio is less than 0.30, the magnetic properties are not sufficiently improved. 411 / S tot is 0.40 or more, more preferably 0.50 or more. 411 / S tot A situation where the ratio is 1.00 means that all of the crystal structure is composed of grains with the {411} orientation, and no grains with other orientations are present, and this embodiment also targets this situation.

[0081] As in the first and second embodiments, the relationship between the {411} oriented grains and the {411} oriented grains that are thought to have competed with the {411} oriented grains in strain-induced grain growth is also important. 411 / S tra When the area ratio S is sufficiently large, the dominance of the {411} oriented grains is ensured even in the situation of normal grain growth after strain-induced grain growth, resulting in good magnetic properties. 411 / S tra If the area ratio S is less than 0.60, the {411} oriented grains do not develop sufficiently due to strain-induced grain growth, and grains with small Taylor factors other than the {411} oriented grains grow to a considerable extent in the normal grain growth state after strain-induced grain growth, and the in-plane anisotropy of the magnetic properties also increases. 411 / S tra is set to 0.60 or more. It is preferable that the area ratio S 411 / S tra is 0.70 or more, more preferably 0.80 or more. 411 / S tra There is no need to particularly limit the upper limit, and all grains having a Taylor factor of 2.8 or less may be grains having the {411} orientation.

[0082] Even in a metal structure in which strain-induced grain growth and subsequent normal grain growth have progressed sufficiently and the strain in the steel sheet is almost released, the grain size for each crystal orientation has a significant effect on the magnetic properties. The {411} orientation grains that grow preferentially at the time of strain-induced grain growth become coarse grains even after normal grain growth. In this embodiment, the relationship between the average grain size satisfies the formulas (23) and (24). d 411 / d ave ≧0.95 (23) d 411 / d tyl ≧0.95 (24)

[0083] These formulas are the average grain size of {411} oriented grains, d 411 is 0.95 times or more the average crystal grain size of other grains. These ratios in formulas (23) and (24) are preferably 1.00 or more, more preferably 1.10 or more, and even more preferably 1.20 or more. There are no particular limitations on the upper limits of these ratios, but during normal grain growth, crystal grains other than {411} oriented grains also grow, but at the point where normal grain growth begins, that is, at the point where strain-induced grain growth ends, the {411} oriented grains become coarse and have a so-called size advantage. Since coarsening is advantageous for {411} oriented grains even during the normal grain growth process, the above ratios remain in a sufficiently characteristic range. Therefore, the practical upper limit is about 10.00. If any of these ratios exceed 10.00, the grains become mixed grains, which may cause problems related to processing such as punchability.

[0084] Furthermore, in terms of the average crystal grain size, it is preferable that the following formula (25) is also satisfied. d 411 / d tra ≧0.95 (25)

[0085] This formula is the average grain size d of the grains with the {411} orientation, which is the preferred growth orientation. 411 is relatively large. The ratio in formula (25) is more preferably 1.00 or more, even more preferably 1.10 or more, and particularly preferably 1.20 or more. There is no particular upper limit to this ratio, but during normal grain growth, crystal grains other than {411} oriented grains also grow, but at the point where normal grain growth begins, that is, at the point where strain-induced grain growth ends, the {411} oriented grains become coarse and have a so-called size advantage. Since coarsening is advantageous for {411} oriented grains even during the normal grain growth process, the above ratio remains in a sufficiently characteristic range. Therefore, the practical upper limit is about 10.00. If any of these ratios exceed 10.0, the grains will become mixed grains, which may cause problems related to processing such as punchability.

[0086] Although the range of the average crystal grain size is not particularly limited, if the average crystal grain size becomes too coarse, it becomes difficult to avoid the deterioration of the magnetic properties. For this reason, as in the second embodiment, the practical average crystal grain size of the {411} orientation grains, which are relatively coarse grains in this embodiment, is preferably 500 μm or less. More preferably, the average crystal grain size of the {411} orientation grains is 400 μm or less, even more preferably 300 μm or less, and particularly preferably 200 μm or less. On the other hand, the lower limit of the average crystal grain size of the {411} orientation grains is preferably 40 μm or more, more preferably 60 μm or more, and even more preferably 80 μm or more, assuming that sufficient preferential growth of the {411} orientation is ensured.

[0087] In equation (24), if there are no crystal grains having an orientation corresponding to the denominator, the equation is not evaluated numerically and is considered to be satisfied.

[0088] [Characteristics] The non-oriented electrical steel sheet according to this embodiment has a controlled chemical composition and metal structure as described above, and therefore has excellent magnetic properties (low iron loss) not only on average in the rolling direction and width direction, but also on average around the circumference (on average in the rolling direction, width direction, 45° direction relative to the rolling direction, and 135° direction relative to the rolling direction). The rolling direction and width direction referred to here are the rolling direction and width direction of the obtained non-oriented electrical steel sheet.

[0089] Magnetic measurements may be performed according to the methods described in JIS C 2550-1 (2011) and JIS C 2550-3 (2019), or according to the method described in JIS C 2556 (2015). If the sample is too small to be measured according to the above JIS standards, the electromagnetic circuit may be measured using a 55 mm square test piece conforming to JIS C 2556 (2015) or a device capable of measuring even smaller test pieces.

[0090] Next, a method for manufacturing a non-oriented electrical steel sheet according to the present embodiment will be described. In the present embodiment, a grain-oriented electrical steel sheet is used as a raw material, and a cold rolling process in the width direction, an intermediate annealing process, and a skin pass rolling process are performed.

[0091] First, a grain-oriented electromagnetic steel sheet having the above-mentioned chemical composition is used as a material to be subjected to cold rolling. The grain-oriented electromagnetic steel sheet may be one manufactured by a known method as long as it has the above-mentioned chemical composition. In other words, a grain-oriented electromagnetic steel sheet manufactured by a known method (for example, a grain-oriented electromagnetic steel sheet satisfying JIS C 2553 (2019) or a product made to each steel company's own standard) may be used. The grain-oriented electromagnetic steel sheet is manufactured through a slab heating process, a hot rolling process, a cold rolling process, a decarburization annealing process, a nitriding treatment, a finish annealing process, etc. The thickness of the grain-oriented electromagnetic steel sheet to be subjected to cold rolling in the width direction is preferably 0.27 to 0.35 mm. In addition, instead of the grain-oriented electromagnetic steel sheet, a material obtained by cutting Goss-oriented grains into a plate shape from a single crystal produced using a material having the above-mentioned chemical composition may be used.

[0092] In the cold rolling process, the grain-oriented electrical steel sheet as described above is cold-rolled at a rolling reduction (cumulative rolling reduction) of 20 to 50% in the width direction of the grain-oriented electrical steel sheet (cold rolling process). If the rolling reduction in the width direction is less than 20%, crystal rotation hardly occurs, and the orientation that serves as the nucleus of the {411} recrystallized grains cannot be formed. If the rolling reduction exceeds 50%, the distortion of the steel sheet becomes too large, and the nucleus of the {411} recrystallized grains changes to the nucleus of the {111} recrystallized grains. The rolling reduction in the width direction in cold rolling is preferably 30 to 40%. Grain-oriented electrical steel sheets are {110} <001> The grains are mainly oriented in the {110} direction. <110> It serves as a direction. {110} <110> When the orientation is rolled and recrystallized, the {411} orientation can appear, and this mechanism is utilized in this embodiment. The width direction of grain-oriented electrical steel sheets is the direction at 90 degrees to the rolling marks, and is determined by the rolling marks. In the case of cutting from a single crystal, <110> The same rolling as above is carried out in a direction parallel to the direction of grain boundary, and then recrystallization is carried out.

[0093] After the cold rolling is completed, intermediate annealing is performed (intermediate annealing step). In this embodiment, for example, intermediate annealing is performed at a temperature of 650°C or higher. If the intermediate annealing temperature is less than 650°C, recrystallization does not occur, the {411} oriented grains do not grow sufficiently, the magnetic flux density does not increase, and the effect of improving iron loss may not be sufficiently obtained. Therefore, the intermediate annealing temperature is set to 650°C or higher. There is no upper limit for the intermediate annealing temperature, but if the intermediate annealing temperature exceeds 900°C, the crystal grains become too large, which makes it difficult for them to grow during the subsequent skin pass rolling and strain-induced grain growth, and makes it difficult to grow the {411} oriented grains. Therefore, the intermediate annealing temperature is preferably set to 650 to 900°C. The annealing time (holding time) is preferably 1 to 60 seconds. If the annealing time is less than 1 second, the time for recrystallization is too short, and the {411} oriented grains may not grow sufficiently. If the annealing time is more than 60 seconds, it is undesirable because it increases costs unnecessarily.

[0094] After the intermediate annealing is completed, skin pass rolling is then performed (skin pass rolling process). As described above, if rolling is performed in a state where there are many {411} oriented grains, the {411} oriented grains will grow further. It is preferable to perform skin pass rolling in the same direction as the above-mentioned cold rolling (the width direction of the grain-oriented electrical steel sheet), and the rolling reduction ratio of the skin pass rolling at this time is 5% to 30%. If the rolling reduction ratio is less than 5%, it is not possible to eliminate the variation in sheet thickness caused by cold rolling in the width direction. In addition, if the rolling reduction ratio exceeds 30%, the {411} oriented grains do not grow, and the {111} oriented grains with poor magnetic properties grow.

[0095] Next, a first heat treatment is carried out to promote strain-induced grain growth (first heat treatment step). The first heat treatment is preferably carried out at 700 to 950° C. for 1 to 100 seconds. If the heat treatment temperature is less than 700° C., strain-induced grain growth does not occur. If the heat treatment temperature exceeds 950° C., not only strain-induced grain growth but also normal grain growth occurs, making it impossible to obtain the metal structure described in the above-mentioned second embodiment. Moreover, if the heat treatment time (holding time) is more than 100 seconds, the production efficiency drops significantly, which is not practical. Since it is not industrially easy to make the holding time less than 1 second, the holding time is set to 1 second or more. The first heat treatment step may be omitted, that is, after the skin pass rolling step, the first heat treatment may be omitted and a second heat treatment, which will be described later, may be performed.

[0096] The non-oriented electrical steel sheet after the skin pass rolling step or the first heat treatment step is subjected to a second heat treatment (second heat treatment step). The second heat treatment step is preferably performed for 1 to 100 seconds when the temperature range is 950 to 1050°C, or for more than 1000 seconds when the temperature range is 700 to 900°C. By performing heat treatment within the above temperature range and time, normal grain growth occurs after strain-induced grain growth when the first heat treatment is omitted, and normal grain growth occurs when the first heat treatment is performed. Depending on the conditions of the first heat treatment, strain-induced grain growth may also occur in the subsequent second heat treatment.

[0097] The non-oriented electrical steel sheet according to the present embodiment can be manufactured as described above. However, this manufacturing method is merely one example of a method for manufacturing the non-oriented electrical steel sheet according to the present embodiment, and is not intended to limit the manufacturing method. EXAMPLES

[0098] Next, the non-oriented electrical steel sheet of the present invention will be specifically described with reference to examples. The examples shown below are merely examples of the non-oriented electrical steel sheet of the present invention, and the non-oriented electrical steel sheet of the present invention is not limited to the following examples.

[0099] (First embodiment) Materials (base materials) with the chemical compositions shown in Tables 1A and 1C were prepared and used as test materials. (Nos. 116 and 151 are non-oriented electrical steel sheets. Nos. 117 to 150 are materials cut into plates from single crystals with Goss-oriented grains. The others are oriented electrical steel sheets.) Here, the left side of equation (1) refers to the value of the left side of equation (1) mentioned above. After that, the material was cut in the width direction (in the case of cutting from a single crystal, <110> The grain-oriented electrical steel sheets were cold-rolled in the width direction (parallel to the direction of the sheet) to obtain cold-rolled sheets. The insulating coating was removed from the grain-oriented electrical steel sheets, and then the cold-rolled sheets were cold-rolled in the width direction. The reduction ratios of the cold rolling are shown in Tables 1B and 1D.

[0100] The cold-rolled sheet was subjected to intermediate annealing in a non-oxidizing atmosphere at the temperatures shown in Tables 1B and 1D for 30 seconds, and then subjected to a second cold rolling (skin pass rolling) at the rolling reduction shown in Tables 1B and 1D. This skin pass rolling was performed in the same direction as the above cold rolling.

[0101] Next, to investigate the texture, a part of the steel sheet was cut, the cut specimen was processed to reduce the thickness to half, and the processed surface (surface parallel to the steel sheet surface) was observed by EBSD (step interval: 100 nm) as described above. The areas and average KAM values ​​of the oriented grains of the types shown in Tables 2A and 2B were obtained by EBSD observation.

[0102] The steel sheets were also subjected to a second heat treatment, annealing at 800°C for 2 hours. From the steel sheets after the second heat treatment, 55 mm square specimens were taken as measurement samples. At this time, a specimen with one side parallel to the rolling direction and a specimen with a 45 degree inclination to the rolling direction were taken. The specimens were taken using a shearing machine. The magnetic properties of the iron loss W10 / 400 (the average value of the energy loss in the rolling direction and width direction that occurred in the test piece when excited at a maximum magnetic flux density of 1.0T and a frequency of 400Hz) and W10 / 400 (all circumference) (the average value of the energy loss in the rolling direction, width direction, 45 degree direction to the rolling direction, and 135 degree direction to the rolling direction that occurred in the test piece when excited at a maximum magnetic flux density of 1.0T and a frequency of 400Hz) were measured in accordance with JISC2556 (2015). The measurement results are shown in Tables 2A and 2B.

[0103] [Table 1A]

[0104] [Table 1B]

[0105] [Table 1C]

[0106] [Table 1D]

[0107] [Table 2A]

[0108] [Table 2B]

[0109] The underlines in Tables 1A to 1D and Tables 2A and 2B indicate conditions outside the scope of the present invention. All of the invention examples Nos. 101 to 110, 117 to 138, and 148 to 150 had good iron loss W10 / 400 and W10 / 400 (all circumference). On the other hand, the comparative examples No. 111 to No. 116 did not satisfy formula (1) or did not satisfy at least one of formulas (3) to (6) because at least one of the intermediate annealing temperature, the cold rolling reduction rate, and the skin pass rolling reduction rate was not optimal. As a result, the iron losses W10 / 400 and W10 / 400 (all circumference) were high. In addition, the comparative examples Nos. 139 to 147 had chemical compositions outside the range of the present invention, and therefore either cracks occurred during cold rolling or they did not satisfy the formulas (3) and (4). As a result, the iron losses W10 / 400 and W10 / 400 (all circumference) were high. In addition, since No. 151, which is a comparative example, used a non-oriented electrical steel sheet as the raw material (base material), it satisfied the chemical composition, the temperature in intermediate annealing, the reduction rate in cold rolling, and the reduction rate in skin pass rolling. However, it did not satisfy the formulas (3) to (4). As a result, the iron losses W10 / 400 and W10 / 400 (all circumference) were high.

[0110] (Second Example) Materials with the chemical compositions shown in Tables 3A and 3C were produced (only No. 217 is a non-oriented electrical steel sheet, Nos. 224 to 248 are materials cut into plates from Goss-oriented grains of single crystals, and the others are oriented electrical steel sheets). Here, the left side of equation (1) refers to the value of the left side of equation (1) mentioned above. After that, the material was cut in the width direction (in the case of cutting from a single crystal, <110> The grain-oriented electrical steel sheets were cold-rolled in the width direction (parallel to the rolling direction) to obtain cold-rolled sheets. The insulating coating was removed from the grain-oriented electrical steel sheets produced, and then cold-rolled in the width direction. The cold-rolling reduction ratios at that time are shown in Tables 3B and 3D.

[0111] The cold-rolled sheet was subjected to intermediate annealing in a non-oxidizing atmosphere at the temperatures shown in Tables 3B and 3D for 30 seconds, and then subjected to a second cold rolling (skin pass rolling) at the rolling reduction shown in Tables 3B and 3D. This skin pass rolling was performed in the same direction as the above cold rolling.

[0112] In order to investigate the texture after skin pass rolling, a part of the steel sheet was cut and the cut specimen was processed to reduce the thickness to half, and the processed surface was observed by EBSD (step interval: 100 nm) as described above. The area and average KAM value of each orientation grain were obtained by EBSD observation, and S tyl / S tot , S 411 / S tot , S 411 / S tra , K 411 / K tyl The results are shown in Tables 3B and 3D.

[0113] Next, the first heat treatment was performed under the conditions shown in Tables 3B and 3D. After the first heat treatment, a part of the steel sheet was cut out and the cut test piece was reduced in thickness to 1 / 2 in order to investigate the texture, and the cut surface was observed by EBSD in the above-mentioned manner. The area, average KAM value, and average grain size of the types shown in Tables 4A and 4B were obtained by EBSD observation.

[0114] The steel sheet was also subjected to a second heat treatment, which involved annealing at a temperature of 800°C for 2 hours. From the steel sheet after the second heat treatment, a 55 mm square sample was taken as a measurement sample. At this time, a sample with one side of the sample parallel to the rolling direction and a sample with a 45 degree inclination to the rolling direction were taken. The samples were also taken using a shearing machine. Then, as in the first embodiment, the magnetic properties of iron loss W10 / 400 (average value in the rolling direction and width direction) and W10 / 400 (all circumference) (average value in the rolling direction, width direction, 45 degree direction to the rolling direction, and 135 degree direction to the rolling direction) were measured. The measurement results are shown in Tables 4A and 4B.

[0115] [Table 3A]

[0116] [Table 3B]

[0117] [Table 3C]

[0118] [Table 3D]

[0119] [Table 4A]

[0120] [Table 4B]

[0121] The underlines in Tables 3A to 3D and Tables 4A and 4B indicate conditions outside the range of the present invention. All of the invention examples Nos. 201 to 210 and Nos. 218 to 239 had good iron loss W10 / 400 and W10 / 400 (all circumference). On the other hand, comparative examples No. 211 to No. 217 did not satisfy formula (1) or did not satisfy any of formulas (10) to (15) because at least one of the temperature in the intermediate annealing, the reduction in the cold rolling, the reduction in the skin pass rolling, and the temperature in the first heat treatment was not optimal. As a result, the iron losses W10 / 400 and W10 / 400 (all circumference) were high. In addition, the comparative examples Nos. 240 to 248 had chemical compositions outside the range of the present invention, and therefore either cracks occurred during cold rolling or they did not satisfy the formulas (10) and (11). As a result, the iron losses W10 / 400 and W10 / 400 (all circumference) were high.

[0122] (Third Example) Materials with the chemical compositions shown in Tables 5A and 5C were produced (only No. 316 is a non-oriented electrical steel sheet, Nos. 317 to 342 are materials cut into plates from single crystals with Goss-oriented grains, and the others are grain-oriented electrical steel sheets). Here, the left side of equation (1) refers to the value of the left side of equation (1) mentioned above. After that, the material was cut in the width direction (in the case of cutting from a single crystal, <110> The grain-oriented electrical steel sheets were cold-rolled in the width direction (parallel to the rolling direction) to obtain cold-rolled sheets. The insulating coating was removed from the grain-oriented electrical steel sheets, and then the cold-rolled sheets were cold-rolled in the width direction. The reduction ratios of the cold rolling are shown in Tables 5B and 5D.

[0123] The cold-rolled sheet was subjected to intermediate annealing in a non-oxidizing atmosphere at the temperatures shown in Tables 5B and 5D for 30 seconds, and then subjected to a second cold rolling (skin pass rolling) at the rolling reduction shown in Tables 5B and 5D. This skin pass rolling was performed in the same direction as the above cold rolling.

[0124] In order to investigate the texture after skin pass rolling, a part of the steel sheet was cut and the cut specimen was processed to reduce the thickness to half, and the processed surface was observed by EBSD (step interval: 100 nm) as described above. The area and average KAM value of each orientation grain were obtained by EBSD observation, and S tyl / S tot , S 411 / S tot , S 411 / S tra , K 411 / K tyl The results are shown in Tables 5B and 5D.

[0125] Next, the second heat treatment was performed under the conditions shown in Tables 5B and 5D without performing the first heat treatment. After the second heat treatment, a part of the steel sheet was cut out, and the cut test piece was reduced in thickness to 1 / 2 in order to investigate the texture, and the cut surface was observed by EBSD. The area and average grain size of the types shown in Table 6 were obtained by EBSD observation.

[0126] After the second heat treatment, 55 mm square specimens were taken from the steel sheets after the second heat treatment as measurement specimens. At this time, a specimen with one side parallel to the rolling direction and a specimen with a 45 degree inclination to the rolling direction were taken. The specimens were taken using a shearing machine. Then, as in the first embodiment, the magnetic properties of iron loss W10 / 400 (average value in the rolling direction and width direction) and W10 / 400 (all circumference) (average value in the rolling direction, width direction, 45 degree direction to the rolling direction, and 135 degree direction to the rolling direction) were measured. The measurement results are shown in Table 6.

[0127] [Table 5A]

[0128] [Table 5B]

[0129] [Table 5C]

[0130] [Table 5D]

[0131] [Table 6]

[0132] The underlines in Tables 5A to 5D and 6 indicate conditions outside the range of the present invention. All of the invention examples Nos. 301 to 310, 317 to 332, and 342 had good iron loss W10 / 400 and W10 / 400 (all circumference). On the other hand, the comparative examples Nos. 311 to 316 did not satisfy formula (1) or did not satisfy at least one of formulas (20) to (24) because at least one of the intermediate annealing temperature, the cold rolling reduction rate, and the skin pass rolling reduction rate was not optimal. As a result, the iron losses W10 / 400 and W10 / 400 (all circumference) were high. In addition, the comparative examples Nos. 333 to 341 had chemical compositions outside the range of the present invention, and therefore either cracks occurred during cold rolling or the formulas (20) and (21) were not satisfied. As a result, the iron losses W10 / 400 and W10 / 400 (all circumference) were high.

[0133] (Fourth Example) Materials with the chemical compositions shown in Tables 7A and 7C were produced (only No. 416 is a non-oriented electrical steel sheet, Nos. 423 to 248 are materials cut into plates from single crystals with Goss-oriented grains, and the others are oriented electrical steel sheets). Here, the left side of equation (1) refers to the value of the left side of equation (1) above. After that, the material was cut in the width direction (in the case of cutting from a single crystal, <110> The grain-oriented electrical steel sheets were cold-rolled in the width direction (parallel to the direction of the sheet) to obtain cold-rolled sheets. The insulating coating was removed from the grain-oriented electrical steel sheets, and then the cold-rolled sheets were cold-rolled in the width direction. The reduction ratios of the cold rolling are shown in Tables 7B and 7D.

[0134] The cold-rolled sheet was subjected to intermediate annealing in a non-oxidizing atmosphere at the temperatures shown in Tables 7B and 7D for 30 seconds, and then subjected to a second cold rolling (skin pass rolling) at the rolling reduction shown in Tables 7B and 7D. This skin pass rolling was performed in the same direction as the above cold rolling.

[0135] Next, the first heat treatment was carried out at 800° C. for 30 seconds. After the first heat treatment, a part of the steel sheet was cut out and the thickness of the cut out test piece was reduced to half, and the cut surface was observed by EBSD (step interval: 100 nm) as described above in order to investigate the texture. The area, average KAM value and average crystal grain size of each type of orientation grain were obtained by EBSD observation, and S tyl / S tot , S 411 / S tot , S 411 / S tra , K 411 / K tyl , d 411 / d ave , d 411 / d tyl asked for.

[0136] The steel sheets after the first heat treatment were subjected to a second heat treatment under the conditions shown in Tables 7B and 7D. After the second heat treatment, a part of the steel sheet was cut out, and the cut specimen was reduced in thickness to 1 / 2 in order to investigate the texture. The cut surface was observed by EBSD. The areas and average grain sizes of the types shown in Table 8 were obtained by EBSD observation.

[0137] In addition, 55 mm square specimens were taken from the steel sheets after the second heat treatment as measurement specimens. At this time, a specimen with one side parallel to the rolling direction and a specimen with one side inclined at 45 degrees to the rolling direction were taken. The specimens were taken using a shearing machine. Then, as in the first embodiment, the magnetic properties of iron loss W10 / 400 (average value in the rolling direction and width direction) and W10 / 400 (all circumference) (average value in the rolling direction, width direction, 45 degrees to the rolling direction, and 135 degrees to the rolling direction) were measured. The measurement results are shown in Table 8.

[0138] [Table 7A]

[0139] [Table 7B]

[0140] [Table 7C]

[0141] [Table 7D]

[0142] [Table 8]

[0143] The underlines in Tables 7A to 7D and Table 8 indicate conditions outside the range of the present invention. All of the invention examples Nos. 401 to 410, 417, 419, 420, 423 to 438, and 448 had good iron loss W10 / 400 and W10 / 400 (all circumference). On the other hand, in the comparative examples Nos. 411 to 416, at least one of the following was not optimal: formula (1), the temperature in the intermediate annealing, the reduction in the cold rolling, or the reduction in the skin pass rolling; therefore, at least one of formulas (20) to (24) was not satisfied. As a result, the iron losses W10 / 400 and W10 / 400 (all circumference) were high. In addition, the comparative examples Nos. 418, 421, and 422 did not satisfy at least one of the formulas (20) to (24) because the temperature or time of the second heat treatment was not optimal. As a result, the iron losses W10 / 400 and W10 / 400 (all circumference) were high. In addition, the comparative examples Nos. 439 to 447 had chemical compositions outside the range of the present invention, and therefore either cracks occurred during cold rolling or the formulas (20) and (21) were not satisfied, resulting in high iron losses W10 / 400 and W10 / 400 (all circumference).

[0144] (Fifth Example) Grain-oriented electrical steel sheets having the chemical compositions shown in Table 9A were produced. Here, the left side of equation (1) represents the value of the left side of equation (1) above. Thereafter, the insulating coating was removed from the grain-oriented electrical steel sheets produced, and the sheets were cold-rolled in the width direction. The reduction ratio of the cold rolling at that time is shown in Table 9B.

[0145] The cold-rolled sheet was subjected to intermediate annealing in a non-oxidizing atmosphere at the temperature shown in Table 9B for 30 seconds, and then subjected to a second cold rolling (skin pass rolling) at the rolling reduction shown in Table 9B. This skin pass rolling was performed in the same direction as the previous cold rolling.

[0146] Next, to investigate the texture, a part of the steel sheet was cut, the cut specimen was processed to reduce the thickness to half, and the processed surface was observed by EBSD (step interval: 100 nm). The areas and average KAM values ​​of the types shown in Table 10 were obtained by EBSD observation.

[0147] The steel sheet was also subjected to a second heat treatment, annealing at 800°C for 2 hours. From the steel sheet after the second heat treatment, a 55 mm square sample was taken as a measurement sample. At this time, a sample with one side of the sample parallel to the rolling direction and a sample with a 45 degree inclination to the rolling direction were taken. The samples were also taken using a shearing machine. Then, as in the first embodiment, the magnetic properties of iron loss W10 / 400 (average value in the rolling direction and width direction) and W10 / 400 (all circumference) (average value in the rolling direction, width direction, 45 degree direction to the rolling direction, and 135 degree direction to the rolling direction) were measured. The measurement results are shown in Table 10.

[0148] [Table 9A]

[0149] [Table 9B]

[0150] [Table 10]

[0151] All of the inventive examples No. 501 to No. 518 satisfied the formulas (3) to (9), and all of them had good values ​​for iron loss W10 / 400 and W10 / 400 (all circumference). [Industrial Applicability]

[0152] According to the present invention, it is possible to provide a non-oriented electrical steel sheet capable of obtaining excellent magnetic properties on average all around, and a manufacturing method thereof. Therefore, the present invention has high industrial applicability.< / uvw>

Claims

1. In mass percent, C: 0.0100% or less, Si: 1.50% to 4.00%, One or more selected from the group consisting of Mn, Ni, Co, Pt, Pb, Cu, and Au: less than 2.50% in total; sol. Al: 4.000% or less, S: 0.0400% or less, N: 0.0100% or less, Sn: 0.00% to 0.40%, Sb: 0.00% to 0.40%, P: 0.00% to 0.40%, Cr: 0.000% to 0.100%, B: 0.0000% to 0.0050%, O: 0.0000% to 0.0200%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; When the Mn content (mass%) is [Mn], the Ni content (mass%) is [Ni], the Co content (mass%) is [Co], the Pt content (mass%) is [Pt], the Pb content (mass%) is [Pb], the Cu content (mass%) is [Cu], the Au content (mass%) is [Au], the Si content (mass%) is [Si], and the sol. Al content (mass%) is [sol. Al], the following formula (1) is satisfied, The balance has a chemical composition consisting of Fe and impurities, Furthermore, when observed by EBSD on a surface parallel to the steel sheet surface, the total area is S tot , the area of ​​the {411} oriented grain is S 411 The area of ​​the oriented grains whose Taylor factor M according to the following formula (2) is greater than 2.8 is defined as S tyl The total area of ​​oriented grains with the Taylor factor M of 2.8 or less is defined as S tra The average KAM value of the {411} oriented grains is K 411 The average KAM value of the oriented grains having the Taylor factor M of more than 2.8 is K tyl The base sheet for a non-oriented electrical steel sheet is characterized in that, when ([Mn]+[Ni]+[Co]+[Pt]+[Pb]+[Cu]+[Au])-([Si]+[sol.Al])≦0.00%...(1) M=(cosφ×cosλ) -1 ・・・(2) 0.20≦S tyl / S tot ≦0.85 ・・・(3) 0.05≦S 411 / S tot ≦0.80 ・・・(4) S 411 / S tra ≧0.50 ・・・(5) K 411 / K tyl ≦0.990 ・・・(6) Here, in formula (2), φ represents the angle between the stress vector and the slip direction vector of the crystal, and λ represents the angle between the stress vector and the normal vector of the slip plane of the crystal.

2. Furthermore, the average KAM value of the oriented grains having the Taylor factor M of 2.8 or less is K tra 2. The base sheet for the non-oriented electrical steel sheet according to claim 1, wherein the following formula (7) is satisfied: K 411 / K tra <1.010 ・・・(7)

3. Furthermore, the area of ​​the {110} oriented grains is S 110 3. The base sheet for the non-oriented electrical steel sheet according to claim 1 or 2, wherein the following formula (8) is satisfied when S 411 / S 110 ≧1.00 ・・・(8) Here, equation (8) is the area ratio S 411 / S 110 It is assumed that this holds true even if diverges to infinity.

4. Furthermore, the average KAM value of the {110} oriented grains is 110 The base sheet for the non-oriented electrical steel sheet according to any one of claims 1 to 3, characterized in that the following formula (9) is satisfied when K 411 / K 110 <1.010 ・・・(9)

5. In mass percent, C: 0.0100% or less, Si: 1.50% to 4.00%, One or more selected from the group consisting of Mn, Ni, Co, Pt, Pb, Cu, and Au: less than 2.50% in total; sol. Al: 4.000% or less, S: 0.0400% or less, N: 0.0100% or less, Sn: 0.00% to 0.40%, Sb: 0.00% to 0.40%, P: 0.00% to 0.40%, Cr: 0.000% to 0.100%, B: 0.0000% to 0.0050%, O: 0.0000% to 0.0200%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; When the Mn content (mass%) is [Mn], the Ni content (mass%) is [Ni], the Co content (mass%) is [Co], the Pt content (mass%) is [Pt], the Pb content (mass%) is [Pb], the Cu content (mass%) is [Cu], the Au content (mass%) is [Au], the Si content (mass%) is [Si], and the sol. Al content (mass%) is [sol. Al], the following formula (1) is satisfied, The balance has a chemical composition consisting of Fe and impurities, Furthermore, when observed by EBSD on a surface parallel to the steel sheet surface, the total area is S tot , the area of ​​the {411} oriented grain is S 411 The area of ​​the oriented grains whose Taylor factor M according to the following formula (2) is greater than 2.8 is defined as S tyl The total area of ​​oriented grains with the Taylor factor M of 2.8 or less is defined as S tra The average KAM value of the {411} oriented grains is K 411 The average KAM value of the oriented grains having the Taylor factor M of more than 2.8 is K tyl , the average grain size in the observation area is d ave The average grain size of the {411} oriented grains is d 411 The average crystal grain size of the oriented grains having the Taylor factor M of more than 2.8 is d tyl The base sheet of a non-oriented electrical steel sheet is characterized in that, when ([Mn]+[Ni]+[Co]+[Pt]+[Pb]+[Cu]+[Au])-([Si]+[sol.Al])≦0.00%...(1) M=(cosφ×cosλ) -1 ・・・(2) S tyl / S tot ≦0.70 ・・・(10) 0.20≦S 411 / S tot ・・・(11) S 411 / S tra ≧0.55 ・・・(12) K 411 / K tyl ≦1.010 ・・・(13) d 411 / d ave >1.00 ・・・(14) d 411 / d tyl >1.00 ・・・(15) Here, in formula (2), φ represents the angle between the stress vector and the slip direction vector of the crystal, and λ represents the angle between the stress vector and the normal vector of the slip plane of the crystal.

6. Furthermore, the average KAM value of the oriented grains having the Taylor factor M of 2.8 or less is K tra The base sheet for the non-oriented electrical steel sheet according to claim 5, characterized in that the following formula (16) is satisfied when K 411 / K tra <1.010 ・・・(16)

7. Furthermore, the average crystal grain size of the orientation grains where the Taylor factor M is 2.8 or less is defined as d tra The base sheet for the non-oriented electrical steel sheet according to claim 5 or 6, characterized in that the following formula (17) is satisfied when d 411 / d tra >1.00 ・・・(17)

8. Furthermore, the area of ​​the {110} oriented grains is S 110 The base sheet for the non-oriented electrical steel sheet according to any one of claims 5 to 7, characterized in that the following formula (18) is satisfied when S 411 / S 110 ≧1.00 ・・・(18) Here, equation (18) is the area ratio S 411 / S 110 It is assumed that this holds true even if diverges to infinity.

9. Furthermore, the average KAM value of the {110} oriented grains is 110 The base sheet for the non-oriented electrical steel sheet according to any one of claims 5 to 8, characterized in that the following formula (19) is satisfied when K 411 / K 110 <1.010 ・・・(19)

10. The chemical composition, in mass%, Sn: 0.02% to 0.40%, Sb: 0.02% to 0.40%, and The base sheet for the non-oriented electrical steel sheet according to any one of claims 1 to 9, characterized in that it contains one or more elements selected from the group consisting of P: 0.02% to 0.40%.

11. The base sheet for non-oriented electrical steel sheet according to any one of claims 1 to 10, characterized in that the chemical composition contains, by mass%, one or more elements selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0005% to 0.0100% in total.

12. A method for producing a base sheet for a non-oriented electrical steel sheet according to any one of claims 1 to 4, In mass percent, C: 0.0100% or less, Si: 1.50% to 4.00%, One or more selected from the group consisting of Mn, Ni, Co, Pt, Pb, Cu, and Au: less than 2.50% in total; sol. Al: 4.000% or less, S: 0.0400% or less, N: 0.0100% or less, Sn: 0.00% to 0.40%, Sb: 0.00% to 0.40%, P: 0.00% to 0.40%, Cr: 0.000% to 0.100%, B: 0.0000% to 0.0050%, O: 0.0000% to 0.0200%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; When the Mn content (mass%) is [Mn], the Ni content (mass%) is [Ni], the Co content (mass%) is [Co], the Pt content (mass%) is [Pt], the Pb content (mass%) is [Pb], the Cu content (mass%) is [Cu], the Au content (mass%) is [Au], the Si content (mass%) is [Si], and the sol. Al content (mass%) is [sol. Al], the following formula (1) is satisfied, a step of cold rolling a grain-oriented electrical steel sheet having a chemical composition with the balance being Fe and impurities at a rolling reduction of 20% to 50% in the width direction; A step of subjecting the cold-rolled steel sheet to intermediate annealing at a temperature of 650°C or higher; A step of subjecting the steel sheet that has been subjected to the intermediate annealing to skin pass rolling at a rolling reduction of 5% to 30% in the same direction as the rolling direction of the cold rolling; 2. A method for producing a base sheet for a non-oriented electrical steel sheet, comprising the steps of: ([Mn]+[Ni]+[Co]+[Pt]+[Pb]+[Cu]+[Au])-([Si]+[sol.Al])≦0.00%...(1)

13. A method for producing a base sheet for a non-oriented electrical steel sheet according to any one of claims 5 to 9, The base sheet of the non-oriented electrical steel sheet according to any one of claims 1 to 4 is subjected to a heat treatment at a temperature of 700°C to 950°C for 1 second to 100 seconds. A method for producing a base sheet for a non-oriented electrical steel sheet, comprising the steps of:

14. In mass percent, C: 0.0100% or less, Si: 1.50% to 4.00%, One or more selected from the group consisting of Mn, Ni, Co, Pt, Pb, Cu, and Au: less than 2.50% in total; sol. Al: 4.000% or less, S: 0.0400% or less, N: 0.0100% or less, Sn: 0.00% to 0.40%, Sb: 0.00% to 0.40%, P: 0.00% to 0.40%, Cr: 0.000% to 0.100%, B: 0.0000% to 0.0050%, O: 0.0000% to 0.0200%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; When the Mn content (mass%) is [Mn], the Ni content (mass%) is [Ni], the Co content (mass%) is [Co], the Pt content (mass%) is [Pt], the Pb content (mass%) is [Pb], the Cu content (mass%) is [Cu], the Au content (mass%) is [Au], the Si content (mass%) is [Si], and the sol. Al content (mass%) is [sol. Al], the following formula (1) is satisfied, The balance has a chemical composition consisting of Fe and impurities, Furthermore, when observed by EBSD on a surface parallel to the steel sheet surface, the total area is S tot , the area of ​​the {411} oriented grain is S 411 The area of ​​the oriented grains whose Taylor factor M according to the following formula (2) is greater than 2.8 is defined as S tyl The total area of ​​oriented grains with the Taylor factor M of 2.8 or less is defined as S tra , the average grain size in the observation area is d ave The average grain size of the {411} oriented grains is d 411 The average crystal grain size of the oriented grains having the Taylor factor M of more than 2.8 is d tyl A non-oriented electrical steel sheet characterized by satisfying the following formulas (20) to (24): ([Mn]+[Ni]+[Co]+[Pt]+[Pb]+[Cu]+[Au])-([Si]+[sol.Al])≦0.00%...(1) M=(cosφ×cosλ) -1 ・・・(2) S tyl / S tot <0.55 ・・・(20) S 411 / S tot >0.30 ・・・(21) S 411 / S tra ≧0.60 ・・・(22) d 411 / d ave ≧0.95 ・・・(23) d 411 / d tyl ≧0.95 ・・・(24) Here, in formula (2), φ represents the angle between the stress vector and the slip direction vector of the crystal, and λ represents the angle between the stress vector and the normal vector of the slip plane of the crystal.

15. Furthermore, the average crystal grain size of the orientation grains where the Taylor factor M is 2.8 or less is defined as d tra Then, the following formula (25) is satisfied. The non-oriented electrical steel sheet according to claim 14. d 411 / d tra ≧0.95 ・・・(25)

16. A method for producing the non-oriented electrical steel sheet according to claim 14, comprising the steps of: A method for producing a non-oriented electrical steel sheet, comprising subjecting an original sheet of the non-oriented electrical steel sheet according to any one of claims 1 to 11 to a heat treatment at a temperature of 950 ° C. to 1050 ° C. for 1 to 100 seconds, or at a temperature of 700 ° C. to 900 ° C. for more than 1000 seconds.

Citation Information

Patent Citations

  • Production of nonoriented silicon steel sheet having high magnetic flux density and reduced in iron loss

    JP1996143960A

  • Semiprocess nonoriented silicon steel sheet having extremely excellent core loss and magnetic flux density and production method therefor

    JP2002363713A

  • Non-oriented electromagnetic steel sheet and manufacturing method therefor

    JP2006219692A

  • Method for producing non-oriented magnetic steel sheet having high magnetic flux density

    JP2011111658A

  • Method for producing non-oriented electromagnetic steel sheet excellent in magnetic characteristic in rolling direction

    JP2011162821A